2003
DOI: 10.1373/clinchem.2003.022350
|View full text |Cite
|
Sign up to set email alerts
|

IgG Subclass Concentrations in Certified Reference Material 470 and Reference Values for Children and Adults Determined with The Binding Site Reagents

Abstract: Background: There is currently no international reference preparation for IgG subclass (IgGSc) quantification. This situation has led to calibration differences among assays and a variety of reference interval values with consequential difficulties in comparing results. We therefore evaluated IgGSc concentrations in Certified Reference Material 470 (CRM 470). Methods: Pure, polyclonal IgG1, -2, -3, and -4 were prepared from a large serum pool for use as primary standards. The IgG mass in each preparation was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
6
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(125 citation statements)
references
References 18 publications
7
110
6
2
Order By: Relevance
“…Zandian & Jungbauer also used polyclonal IgG for their IgSelect evaluation but did not scrutinize the IgG subclass selectivity (Zandian & Jungbauer, 2009). In contrast to IgSelect, we found that final containers produced with Protein G Sepharose FF showed an IgG subclass distribution similar to the normal IgG subclass distribution in human blood plasma, as expected (Morell et al, 1972, Schauer et al, 2003.…”
Section: Igselect Affinity Resinsupporting
confidence: 66%
See 1 more Smart Citation
“…Zandian & Jungbauer also used polyclonal IgG for their IgSelect evaluation but did not scrutinize the IgG subclass selectivity (Zandian & Jungbauer, 2009). In contrast to IgSelect, we found that final containers produced with Protein G Sepharose FF showed an IgG subclass distribution similar to the normal IgG subclass distribution in human blood plasma, as expected (Morell et al, 1972, Schauer et al, 2003.…”
Section: Igselect Affinity Resinsupporting
confidence: 66%
“…A reduction in the complexity of the manufacturing should also lead to an improved IgG yield, which would increase the market supply needed for new indications like neurological disorders (e.g. Alzheimer's disease (Relkin et al, 2009) (Morell et al, 1972, Schauer et al, 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Total Ig produced in culture supernatants were measured using IgG-, IgA-, and IgM-specific ELISA; Abs used were from Southern Biotech. Certified Reference Material 470 (ERM-DA470, Institute for Reference Materials and Measurements) (43) and human Ig standards (Sigma) were used as standard material for Ig isotype quantification. Intracellular cytokine expression was detected after restimulation of cells with PMA and ionomycin in the presence of 10 mg/ml brefeldin A (Sigma-Aldrich).…”
Section: Elisa Facs Analysis and Intracellular Cytokine Stainingmentioning
confidence: 99%
“…We assessed final purity by SDS-PAGE using silver-staining and enzyme immunoassays (EIAs). We determined subclass distribution by nephelometry (Binding Site Ltd.) and compared results with those in the CRM-470 international serum protein reference material (18 ). We measured concentrations of the purified proteins using the BCA reaction (Pierce Ltd.) and used the results to standardize the specific HLC assays.…”
Section: Reference Materialsmentioning
confidence: 99%